Sodium channels in axons and glial cells of the optic nerve of Necturus maculosa (The Rockefeller University Press, 1979)
Experiments investigating both the binding of radioactively labelled saxitoxin (STX) and the electrophysiological response to drugs that increase the sodium permeability of excitable membranes were conducted in an effort to detect sodium channels in glial cells of the optic nerve of Necturus maculosa, the mudpuppy. Glial cells in nerves from chronically enucleated animals, which lack optic nerve axons, show no saturable uptake of STX whereas a saturable uptake is clearly present in normal optic nerves. The normal nerve is depolarized by aconitine, batrachotoxin, and veratridine (10(-6)-10(-5) M), whereas the all-glial preparation is only depolarized by veratridine and at concentrations greater than 10(-3) M. Unlike the depolarization caused by veratridine in normal nerves, the response in the all-glial tissue is not blocked by tetrodotoxin nor enhanced by scorpion venom (Leiurus quinquestriatus). In glial cells of the normal nerve, where axons are also present, the addition of 10(-5) M veratridine does lead to a transient depolarization; however, it is much briefer than the axonal response to veratridine in this same tissue. This glial response to veratridine could be caused by the efflux of K+ from the drug- depolarized axons, and is similar to the glial response to extracellular K+ accumulation resulting from action potentials in the axon.